Dust Properties of Two New Cavity Structures Nearby Asymptotic Giant Branch Stars: The IRAS Survey - Gautam, Sujan Prasad; Silwal, Ashok; Tiwari, Mijas; Subedi, Seema; Khanal, Manish; Jha, Ajay Kumar (Journal of Institute of Science and Technology, 2021)
We studied the dust properties of two cavity structures (namely FIC21+54 and FIC16-56) nearby Asymptotic Giant Branch stars using Infrared Astronomical Satellite (IRAS) maps. Dust color temperature, Planck function, dust mass, and visual extinction with their distribution within the region of interest were examined. The temperature of dust was found to lie in the range of 22.24 ± 0.81 K to 23.27 ± 0.21 K, and 25.12 ± 0.43 K to 26.17 ± 0.62 K, and the mass of dust was obtained within the range of 4.21 × 1026 kg to 3.6 × 1027 kg, and 2.1 × 1027 kg to 3.31 × 1028 kg, for FIC21+54 and FIC16-56, respectively. Some unusual behaviors on the distribution of dust temperature indicated the effect of nearby sources within the studied structures. Moreover, we observed the trend of dust particles along the major and minor diameters, and plots represented that the particles were oscillating with a sinusoidal pattern in both cavities. The negative slope between 25 µm and 60 µm in far-infrared spectral distribution was encountered for both structures, which portrayed less number density of particles in 60 µm band; interaction between AGB wind and the ambient interstellar medium could be the possible reason behind this. These findings support the prior results for two new cavity structures nearby AGB stars within the galactic plane -10° < b < +10°.